Factors affecting users' satisfaction towards online banking in the northern region of Malaysia - Chong Hui Ling (School of Business Innovation and Technopreneurship, University Malaysia Perlis, 2012)
Online banking was started introduced in Malaysia on 1 June , 2000 due to rapid development of information and communication technology. It allows people to manage and handle their banking account and transactions by using internet facility. However, this system is not fully utilize by Malaysian regarding to the number of people visit to the physical bank is still considered high. This is proved by the statistic of online banking subscribers in Malaysia is not drastically increase compared to the statistic of internet users since 2006 until 2010. Even though online banking services provide advantages for both customers and banker, there are still a large group of customers refusing to use online banking services. Thus, it is important to identify the factors that determine user's satisfaction on using online banking services. In this study, six factors that influenced the satisfaction on using online banking such as self-efficacy, performance expectancy, effort expectancy, social influence, service quality and information quality were selected through literature review.